Assessment of thermal properties of various types of high-strength steels at elevated temperatures. (June 2021) - Xing, Yonghui; Wang, Weiyong; Al-azzani, Hisham
Abstract: Accurate assessment of the thermal properties of steel is a key issue in the fire simulation and design of steel structures. Thermal property tests were conducted for seven types of high-strength steels (HSSs), namely Q460, Q500, Q550, Q620, Q690, Q890, and Q960 steels, along with conventional mild steel Q345. The thermal expansion, specific heat, and thermal conductivity of various steels at a temperature range of 25–1000 °C were obtained and compared to the results proposed by Eurocode 3 and ASCE to validate the applicability of these codes to HSSs. The test results showed that the phase transition temperature of HSS was lower than that of mild steel, and HSS experienced substantial thermal expansion at elevated temperatures. Eurocode 3 and ASCE can be used to approximate the thermal expansion of the HSS only before the phase transition temperature. The endothermic capacity of HSS was weaker than that of mild steel at elevated temperatures. The specific heat of the various types of HSSs could only be effectively predicted by Eurocode 3 and ASCE up to 600 °C, whereas their thermal conductivity could not be reasonably predicted by these codes in temperature range of 25–1000 °C. New equations for thermal expansion, specific heat, and thermal conductivity were proposed to accurately assess the thermal properties of HSS. Graphical abstract: Accurate assessment of the thermal properties of steel is a key issue in the fire simulation and design of steel structures. Thermal property tests were conducted for seven types of high-strength steels (HSSs), namely Q460, Q500, Q550, Q620, Q690, Q890, and Q960 steels, along with conventional mild steel Q345. The thermal expansion, specific heat, and thermal conductivity of various steels at a temperature range of 25–1000 °C were obtained and compared to the results proposed by Eurocode 3 and ASCE to validate the applicability of these codes to HSSs. The test results showed that the phase transition temperature of HSS was lower than that of mild steel, and HSS experienced substantial thermal expansion at elevated temperatures. Eurocode 3 and ASCE can be used to approximate the thermal expansion of the HSS only before the phase transition temperature. The endothermic capacity of HSS was weaker than that of mild steel at elevated temperatures. The specific heat of the various types of HSSs could only be effectively predicted by Eurocode 3 and ASCE up to 600 °C, whereas their thermal conductivity could not be reasonably predicted by these codes in temperature range of 25–1000 °C. New equations for thermal expansion, specific heat, and thermal conductivity were proposed to accurately assess the thermal properties of HSS. Image 1 Highlights: Thermal properties, including thermal expansion, specific heat and thermal conductivity of high strength steels were tested. The thermal properties prediction applicability of EC3 and ASCE to high strength steels were checked. Thermal properties between high strength steel and mild steel were compared. New equations to predict thermal properties of high strength steels were proposed.